Lipid-driven immunometabolic responses in atherosclerosis. Issue 5 (October 2018) - Gisterå, Anton; Ketelhuth, Daniel F.J.
Abstract : Purpose of review: Atherosclerosis is a chronic inflammatory disease in which subendothelial infiltration of lipoproteins leads to inflamed lesions in arteries. Despite improvements in secondary prevention, most cardiovascular events cannot be avoided with current therapies. This review focuses on novel mechanistic insights on lipid-driven immune activation, which could pave the way for new anti-inflammatory treatments for atherosclerosis. Recent findings: Immunometabolic interactions can shape the immune response. Within atherosclerotic plaques, macrophages and T cells are the dominant immune cell populations. Using multiple mechanisms, lipoprotein-derived components activate both the innate and adaptive immune systems. Cholesterol crystals and apolipoprotein B-peptides have been shown to activate macrophages and T cells, respectively. Lipoproteins are also important modulators of regulatory T cells that can hamper vascular inflammation. In the liver, T cells can influence hepatic inflammation and lipoprotein metabolism. Hence, there is an intricate crosstalk between the immune system and lipoprotein metabolism. Summary: Novel treatments are needed to prevent clinical manifestations of atherosclerosis. Improved understanding of lipid-driven immunometabolic responses is likely to reveal new therapeutic targets.